Technology ventures from idea to enterprise - Byers, Thomas (Thomas H.); Dorf, Richard C.; Nelson, Andrew J. (Mc-Graw Hill Education, 2015)
For business, engineering, and science students and professionals who demand a comprehensive guide to high-growth entrepreneurship, this title presents the resource for analyzing opportunities and building new enterprises